Equilibrium Sorption Isotherms of Cr(III) on Sphingomonas sp. XJ2 - Xu, Guo-Xiang; Li, Xu-Qiang; Chen, Wen-Bin (Asian Journal of Chemistry, 2013)
The present study was undertaken to develop a low cost effective adsorbent and adsorption process involved in the adsorption of heavy metal-contaminated industrial wastewater using the developed adsorbent. Sphingomonas sp. XJ2 is an excellent adsorbent for the adsorption efficiency of the chromium(III). Operational parameters such as pH, agitation time and adsorbent dosage, initial ion concentration and temperature were also studied. The optimal pH value for Cr(III) adsorption was 6. The maximum adsorption capacity of Sphingomonas sp. XJ2 for Cr(III) was 3.12 mmol/g. Adsorption data fitted well with the Langmuir and Freundlich models. However, Langmuir isotherm displayed a better fitting model than Freundlich isotherm because of the higher correlation coefficient than the former exhibited. Desorption studies were carried out with HCl, HNO3, EDTA, sodium carbonate and deionization water and quantitative recovery of the metal was evident. The result shows Sphingomonas sp. XJ2 is the excellent adsorbent for Cr(III).